How to Design a Fiscal Strategy in a Resource-Rich Country. (IMF How To Notes; How-To Note, 2021)
This How to Note provides operational guidance for policymakers and IMF staff teams on designing-or revising-a fiscal strategy in resource-rich countries (RRC). Properly managed, resource revenue can support fiscal sustainability and development and equity objectives. Resource revenues also create significant stabilization challenges for fiscal policy because of their size, uncertainty, volatility, and finite nature. The guidance in this note is intended to be general and applicable to RRCs with a range of income levels, resource endowments, and macroeconomic contexts. It is designed primarily to help policymakers analyze the trade-offs associated with alternative fiscal paths and select the right fiscal strategy, given country-specific circumstances.